PENGARUH KONDISI KEUANGAN PERUSAHAAN DAN OPINI AUDIT TERHADAP PERTUMBUHAN PERUSAHAAN (PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Jefri Ariyadi; Sri Lestari Hendrayati; Rini Oktavia (Universitas Palangka Raya, 2021)
This study aims to (1) To analyze the effect of a company's financial condition on company growth, (2) To analyze the effect of audit opinion on company growth and (3) To analyze the effect of company financial condition and audit opinion on company growth. The sample in this study was taken using a purposive sampling technique. A sample of 37 companies from a population of 39 companies in the consumer goods industry sector were listed on the Indonesia Stock Exchange in 2015-2018, so that the research data analyzed amounted to 148. The data analysis technique used was descriptive statistics, classical assumption test, multiple linear regression analysis. The results of the research show that financial condition and audit opinion influence the company's growth partially or simultaneously. Based on the results of this study, the suggestions given are as follows (1) for investors to invest in companies that receive unqualified opinion. In addition to this, it is also necessary to pay attention to the company's financial condition which will have an impact on the company's growth. (2) For future researchers to include other variables such as other financial ratios, size, quality of auditors and extend the year of observation